4CPS-215 Access to 'fondo AIFA 5%' as an instrument supporting the sustainability in a shared clinical management of rare and difficult-to-treat diseases. (March 2019) - Valinotti, G; Scaldaferri, M; Tonelli, M; Crosasso, P; Chiappetta, MR; Cattel, F
Abstract : Background: AIFA 5% Fund is a national fund intended to cover costs related to the treatment of rare diseases and other pathologies with orphan drugs or off-label drugs, through a patient-named system of evaluation. Purpose: The aim was to demonstrate how the interdisciplinary activity of the pharmacist can lead to a potential cost-saving. Material and methods: The identification of patients that could access the Fund, took place through direct reporting by the doctor or through evaluation of the pharmacist during the discussion of cases during the interdisciplinary rounds or following the reporting of off-label drugs. The pharmacy had drawn up a special official procedure that provided the key elements for: Requesting the AIFA authorisation. Management of orders and reimbursement by the pharmacy. All these data were collected in a hospital database that is updated for each new request. Results: From July 2017 to September 2018, 52 clinical cases were identified as eligible for the access request: at the moment, 46 cases have been authorised. Cases related to rare diseases reported on 18 March 2017 1 are 13 (membranoproliferative glomerulonephritis, autoimmune hypoparathyroidism, peripheral T-cell lymphoma, gigantocellular arteritis, neuroblastoma, systemic sclerosis). Twenty-two requests came from the nephrology area (eculizumab – membranoproliferative glomerulonephritis, tocilizumab/antibody-mediated chronic rejection), while 12 cases belonged to the haematological area (belinostat – PTCL-U, ibrutinib and ruxolitinib – GVHD, venetoclax – mantellar cell lymphoma, venetoclax +5 azacitidine – leukaemia acute myeloid (LAM), sorafenib – LAM FLT3 +, peg-interferon – essential thrombocythaemia, pembrolizumab – mediastinal lymphoma, bortezomib – post-transplant maintenance in multiple high-risk myeloma). The remaining cases are of relevance to the oncology, paediatric and endocrinological oncology areas. The total amount currently authorised is €2, 049, 425. Conclusion: Since these off-label treatments would be formerly paid for by the hospital, thanks to this path they are instead completely reimbursed by the AIFA 5% Fund. The results obtained demonstrate how the integration of the pharmacist into clinical management obtains an excellent balance between the prescriptive appropriateness and the economic sustainability in rare or highly complex diseases through access to the AIFA Fund 5%. References and/or acknowledgements: 1. Law 326/2003 G.U. 274 25 November 2003. No conflict of interest.